Quantitative assessment of post‐disaster housing recovery: a case study of Punta Gorda, Florida, after Hurricane Charley. Issue 2 (27th December 2012) - Rathfon, Dana; Davidson, Rachel; Bevington, John; Vicini, Alessandro; Hill, Arleen
<x xml:space="preserve">Abstract</x> Quantitative assessment of post‐disaster housing recovery is critical to enhancing understanding of the process and improving the decisions that shape it. Nevertheless, few comprehensive empirical evaluations of post‐disaster housing recovery have been conducted, and no standard measurement methods exist. This paper presents a quantitative assessment of housing recovery in Punta Gorda, Florida, United States, following Hurricane Charley of August 2004, including an overview of the phases of housing recovery, progression of recovery over time, alternative trajectories of recovery, differential recovery, incorporation of mitigation, and effect on property sales. The assessment is grounded in a conceptual framework that considers the recovery of both people and place, and that emphasises recovery as a process, not as an endpoint. Several data sources are integrated into the assessment—including building permits, remotely sensed imagery, and property appraiser data—and their strengths and limitations are discussed with a view to developing a standardised method for measuring and monitoring housing recovery.